AN ANALYSIS OF ACCOUNTING TERMS TRANSLATION IN TEXTBOOK MANAGEMENT ACCOUNTING BY DON R. HANSEN AND MARYANE M. MOWEN INTO AKUNTANSI MANAJAMEN BY DEWI FITRIASARI DAN DENY ARNOS KWARY - Zainal Arifin (Universitas Muhammadiyah Surakarta, 2009)
This study aims at identifying, analyzing and describing the accuracy of accounting terms translation in Textbook ‘Management Accounting’ and its translation ‘Akuntansi Manajemen.’ This study is in the domain of descriptive-qualitative.The data sources are the document, questionnaire and informants, and the datawere the sentences containing the accounting terms. The data are collected bytechniques of the content analysis, in-depth interview and questionnaire. For thevalidity of data, this study used the data triangulation technique, and then the datawere analyzed with the interactive model. The finding of this study shows that from58 data, the accuracy of the accounting terms translation was 53 data or 91.38%while their inaccuracy was 5 data or 8.62%. The other finding shows that not allthe accounting terms were translated but changed in their spellings according tothe rules of spelling adaptation in Indonesian language.Keywords: accounting terms, translation, accuracy